Determinants of Bonanza Episodes and Related Effects on Financial Crises in Emerging Market Countries (International Journal of Business and Development Studies, 2012)
Although capital inflows affect positively economies in long-run, it is possible to generate somehow destructive effects if there is no any control on financial markets. This study tries to explore main determinants of large capital inflows episodes to emerging markets. It is also investigated whether the large capital inflows episodes lead to financial crises in forms of sudden stop phenomenon, currency and banking crises. To this end, annual data for 44 emerging countries have been used during 1970-2011. The empirical results have shown that the lagged period of large capital inflows episodes (so-called as the bonanza phenomenon) and the related contagion are most important variables to explain these phenomena in international capital markets. Overall, the results indicate that herding behavior is a key determinant of bonanza episodes in the selected emerging market countries.